Exploring the factors contributing to the lack of commitment to governance disclosure among Malaysian companies - Mohd Taib, Nursyuhada; Shafaruddin, A. D. Rosilawati; Fauzi, Nuruu Ain; Yuhanis, Nursia (UiTM Cawangan Johor, 2025)
This study aims to explore the factors that contribute to the lack of commitment among companies in Malaysia towards governance disclosure, particularly in efforts to curb the practice of artificial income smoothing. Using a qualitative approach with a Basic Qualitative Inquiry design, five participants consisting of senior managers and executives were interviewed in depth. The study findings indicate four main factors that contribute to this issue, namely lack of management awareness and understanding, an organizational culture that does not support transparency, disclosure as a minimum compliance process, and constraints in terms of structure and implementation guidelines. This study proposes a conceptual model that emphasizes the role of organizational strategic support as a mediator in strengthening the effectiveness of governance disclosure. This study is expected to contribute to the literature and corporate practices related to more transparent and effective governance. Keywords: Corporate Governance, Disclosure, Artificial Income Smoothing, Organizational Commitment, Qualitative Research